Potential of dietary hemp and cannabinoids to modulate immune response to enhance health and performance in animals: opportunities and challenges - Hassan, Faiz-ul; Liu, Chunjie; Mehboob, Maryam; Bilal, Rana Muhammad; Arain, Muhammad Asif; Siddique, Faisal; Chen, Fengming; Li, Yuying; Zhang, Jingmeng; Shi, Pengjun; Lv, Biguang; Lin, Qian (Frontiers in Immunology, 2023)
Cannabinoids are group of compounds that resembles chemical constituents of Cannabis sativa both physiologically and structurally. The active components of cannabis with therapeutic potential are known as cannabinoids. Cannabinoids are divided into three groups: plant-derived cannabinoids (phytocannabinoids), endogenous cannabinoids (endocannabinoids), and synthetic cannabinoids. Cannabinoid receptor type 1 (CB1) stimulates the binding of orexigenic peptides and inhibits the attachment of anorexigenic proteins to hypothalamic neurons in mammals, increasing food intake. Digestibility is unaffected by the presence of any cannabinoids in hemp stubble. Endogenous cannabinoids are also important for the peripheral control of lipid processing in adipose tissue, in addition to their role in the hypothalamus regulation of food intake. Regardless of the kind of synaptic connection or the length of the transmission, endocannabinoids play a crucial role in inhibiting synaptic transmission through a number of mechanisms. Cannabidiol (CBD) mainly influences redox equilibrium through intrinsic mechanisms. Useful effects of cannabinoids in animals have been mentioned e.g., for disorders of the cardiovascular system, pain treatment, disorders of the respiratory system or metabolic disorders. With an emphasis on the poultry and ruminants, this review aims to highlight the properties of cannabinoids and their derivatives as well as their significance as a potential feed additive in their diets to improve health and performance.